2021
DOI: 10.2169/internalmedicine.5893-20
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Response after the Discontinuation of Nivolumab in an Advanced Gastric Cancer Patient

Abstract: A durable response after the discontinuation of immune checkpoint-inhibitor therapy has previously been reported in several cancers. We herein describe a patient with gastric cancer who maintained a durable response after the discontinuation of nivolumab. A 65-year-old man was treated with nivolumab as a sixth-line therapy for recurrent gastric cancer. After four cycles of nivolumab therapy, he showed a partial response. But the treatment was discontinued when two immune-related adverse events occurred after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Consistent with these reports, several studies have demonstrated prolonged remission in patients after the discontinuation of nivolumab therapy (8,17,18). Accordingly, a correlation may be present between long-term PD-1 occupancy and a prolonged treatment effect (9). In our study, two patients experienced disease recurrence after discontinuation of nivolumab.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with these reports, several studies have demonstrated prolonged remission in patients after the discontinuation of nivolumab therapy (8,17,18). Accordingly, a correlation may be present between long-term PD-1 occupancy and a prolonged treatment effect (9). In our study, two patients experienced disease recurrence after discontinuation of nivolumab.…”
Section: Discussionsupporting
confidence: 90%
“…In some reports, long-lasting responses were observed in patients even after discontinuation of nivolumab treatment and no further anti-cancer treatment (8)(9)(10). Although the mechanisms of long-lasting response are not fully understood, prolonged binding of nivolumab on T cells is one possible explanation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…A durable response after ICI discontinuation has also been reported for various tumor entities (22,(26)(27)(28)(29). For R/M-HNSCC the broadly accepted concept is an ICI treatment until disease progression or unacceptable toxicity such as irAE.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, we resumed nivolumab treatment, and QTc prolongation was not observed. Recent studies have also shown that the emergence of irAEs is reportedly associated with better outcomes for ICI treatment in several cancers 19–21 . However, the association between the types of irAEs and the response to ICIs in different cancer types remains unclear.…”
Section: Discussionmentioning
confidence: 99%